K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 10 2015

\(x^2-5x+8=x^2-5x+\frac{25}{4}+\frac{7}{4}=\left(x-\frac{5}{2}\right)^2+\frac{7}{4}\)

Vì   \(\left(x-\frac{5}{2}\right)^2\ge0\Rightarrow\left(x-\frac{5}{2}\right)^2+\frac{7}{4}\ge\frac{7}{4}\)

Mà  \(\frac{7}{4}>0\Rightarrow\left(x-\frac{5}{2}\right)^2+\frac{7}{4}>0\)

Vậy   \(x^2-5x+8>0\)

 

a) (a - b)2 = a2 - 2ab + b2 = a2 + 2ab + b2 - 4ab = (a + b)2 - 4ab

b) x2 + 4x + 9 = x2 + 4x + 4 + 5 = (x + 2)2 + 5

Ta có (x + 2)2 > 0 Vx

\(\Rightarrow\) (x + 2)2 + 5 > 5 > 0 Vx

\(\Rightarrow\) x2 + 4x + 9 > 0 Vx

NV
5 tháng 4 2019

a/ \(x+4y=1\Rightarrow x=1-4y\)

\(A=x^2+4y^2=\left(1-4y\right)^2+4y^2=20y^2-8y+1\)

\(A=20\left(y^2-2.\frac{1}{5}y+\frac{1}{25}\right)+\frac{1}{5}=20\left(y-\frac{1}{5}\right)^2+\frac{1}{5}\ge\frac{1}{5}\)

\(\Rightarrow A_{min}=\frac{1}{5}\) khi \(\left\{{}\begin{matrix}y=\frac{1}{5}\\x=1-4y=\frac{1}{5}\end{matrix}\right.\)

b/

\(B=\frac{2x^2+5x+8}{x}=2x+\frac{8}{x}+5\ge2\sqrt{2x.\frac{8}{x}}+5=13\)

\(\Rightarrow B_{min}=13\) khi \(x=2\)

5 tháng 4 2019

Bạn giúp mình nốt câu c và cau d nha:'<

c) C= (2x2 +6x+10)/(x2+3x+3)

d) D= 4x2 +4x +2/x +15; x>0

31 tháng 8 2020

x2 - 2x + 3 = ( x2 - 2x + 1 ) + 2 = ( x - 1 )2 + 2 ≥ 2 > 0 ∀ x ( đpcm )

x2 - x + 1 = ( x2 - x + 1/4 ) + 3/4 = ( x - 1/2 )2 + 3/4 ≥ 3/4 > 0 ∀ x ( đpcm )

x2 + 4x + 7 = ( x2 + 4x + 4 ) + 3 = ( x + 2 )2 + 3 ≥ 3 > 0 ∀ x ( đpcm )

-x2 + 4x - 5 = -( x2 - 4x + 4 ) - 1 = -( x - 2 )2 - 1 ≤ -1 < 0 ∀ x ( đpcm )

-x2 - x - 1 = -( x2 + x + 1/4 ) - 3/4 = -( x + 1/2 )2 - 3/4 ≤ -3/4 < 0 ∀ x ( đpcm )

-4x2 - 4x - 2 = -4( x2 + x + 1/4 ) - 1 = -4( x + 1/2 )2 - 1 ≤ -1 < 0 ∀ x ( đpcm )

12 tháng 7 2016

a) \(S=25x^2-20x+7=\left[\left(5x\right)^2-2.5x.2+4\right]+3=\left(5x-2\right)^2+3>0\) với mọi x

b) \(P=9x^2-6xy+2y^2+1=\left[\left(3x\right)^2-2.3x.y+y^2\right]+y^2+1=\left(3x-y\right)^2+y^2+1>0\)với mọi x

12 tháng 7 2016

25x2  - 20x + 7 = ( 25x2 - 20x + 4 ) + 3 = (5x-2)2 + 3 > 0

còn câu b, P = 9x2 - 6xy + 2y2 + 1 = (3x-y)2 + y2 + 1 >0